2001
DOI: 10.1021/es010103x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Dissolved Natural Organic Matter (DOM) Mediated Phototransformation of Phenylurea Herbicides in Lakes

Abstract: For many important classes of pesticides including phenylurea herbicides (PUHs) and triazines, photosensitized transformation may be the only relevant elimination process in surface waters. In this study, the dissolved organic matter (DOM) mediated phototransformation of PUHs has been investigated in laboratory and field experiments. The results indicate that, in surface waters, the photosensitized transformation of PUHs may be significant and occurs primarily by an initial one-electron oxidation most likely i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
172
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 13 publications
(14 reference statements)
11
172
0
1
Order By: Relevance
“…The results showed that MeHg compexed with DOM was dramatically decreased in the presence of NaN 3 . This finding suggested that 26,27 can also exist in the aquatic environments and be involved in the photodegradation of different pollutants in water.…”
Section: ■ Introductionmentioning
confidence: 89%
“…The results showed that MeHg compexed with DOM was dramatically decreased in the presence of NaN 3 . This finding suggested that 26,27 can also exist in the aquatic environments and be involved in the photodegradation of different pollutants in water.…”
Section: ■ Introductionmentioning
confidence: 89%
“…However, concentrations involved are much higher than those found in environmental waters. Organic compounds that occur in aqueous environments can be transformed by a variety of abiotic and biological pathways, among which direct photochemistry and photogenerated reactive species such as hydroxyl radical ( • OH), carbonate radical (CO 3 •− ), singlet oxygen ( 1 O 2 ) and triplet states of Chromophoric Dissolved Organic Matter ( 3 CDOM*) (Mack and Bolton, 1999;Canonica et al, 1995 andCanonica and Freiburghaus, 2001;Gerecke et al, 2001;Boreen et al, 2003;Page et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…10 They are used for a variety of purposes, 11 such as systemic herbicides (isoproturon and chlortoluron) to control broadleaf and grassy weeds in cereals and other crops, in cotton fields (linuron), as total herbicides in urban areas (diuron), and as algicides in paints and coatings (diuron). 12 They exhibit a high degree of biotoxicity, have a moderate to low solubility in water, and have received particular attention in recent years because of their toxicity and possible carcinogenic properties, requiring several weeks to months for their removal from the environment. 13 Moreover, diuron and isoproturon are considered The shortage of information in the literature about the chemical oxidation of this important group of pollutants promoted the design of a general research program for the study of the chemical degradation in aqueous solutions by several oxidation treatments of four selected herbicides of this group: linuron (L; 3-(3,4dichlorophenyl)-1-methoxy-1-methylurea), chlortoluron (C; 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea), diuron (D; 3-(3,4-dichlorophenyl)-1,1-dimethylurea), and isoproturon (I; 3-(4-isopropylphenyl)-1-1-dimethylurea).…”
Section: Introductionmentioning
confidence: 99%